Pengaruh Pengungkapan Corporate Social Responsibility, Financial Distress, Company Risk Terhadap Real Earnings Management Dengan Good Corporate Governance Sebagai Variabel Moderasi - Aqamal Haq; Nafisah Azka Al Manar (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the effect of CSR disclosure, financial distress, and company risk on real earnings management, with audit committees (economics background) as moderating variable. Using 30 firms from the basic materials, energy, and infrastructure sectors (2019–2021), results show that CSR disclosure has no effect, while financial distress and company risk positively influence real earnings management. Audit committees weaken the positive effects of financial distress and company risk but do not moderate CSR disclosure.